Politeness Strategies and Its Impact on Character Interactions in Legally Blonde Movie: Pragmatics Study - Aulia Puspita Sari; Ervina CM Simatupang (Universitas Nahdlatul Wathan Mataram, 2024)
This study examines politeness strategies in Legally Blonde (2001) and its impact on character interactions. Based on Brown and Levinson's (1987) politeness theory, identifies and explains the application of positive politeness, negative politeness, bald-on record, and off-record in various situations and contexts. Using descriptive qualitative methodology, it analyzes dialogues to explore how politeness strategies shape interactions and convey meaning.The findings of this study highlight the role of pragmatics in understanding language use, showing how words and expressions can carry different meanings based on context. Practically, this study underscores the importance of politeness strategies in fostering effective communication and maintaining social harmony in diverse environments